Embassies in crisis
1 online resource (x, 255 pages).
Keywords: Embassies are integral to international diplomacy, their staff instrumental to inter-governmental dialogue, strategic partnerships, trading relationships and cultural exchange. But Embassies are also discreet political spaces. Notionally sovereign territory immune' from local jurisdiction, in moments of crisis Embassies have often been targets of protest and sites of confrontation. It is this aspect of Embassy experience that this collection of essays explores and Embassies in Crisis revisits flashpoints in the recent lives of Embassies overseas at times of acute political crisis. Ranging across multiple British and other embassy crises, unusually, this book offers equal insights to international historians and members of the diplomatic community.